Realizing farmers' rights through community seed banks in Uganda: experiences and policy issues - Otieno, G.A.; Kiwuka, C.; Mulumba, John W. (Canadian Center of Science and Education, 2017)
The paper interrogates the role of community seed banks (CSBs) and related initiatives in the realization of farmers' rights in Uganda and the policy and legislative space for the functioning of CSBs. The study finds that although community seed banks are a relatively new phenomenon in Uganda, there have been community based seed banking initiatives that have been instrumental in the realization of farmers' rights to save and exchange seed and information; and especially providing a wide range of diversity of seed to farmers and improving access to good quality seed. Through partnerships with local Non-Governmental Organizations (NGOs), research and government institutions, CSBs have received technical and financial support for conservation and seed production activities, thus enabling them to participate in seed value-chains through production of quality declared seed (QDS) and participate in decision making. Although the policy and legal environment for the functioning of CSBs is not well defined, various pieces of draft legislation provide positively for ways through which CSBs can be recognized and supported for the benefit of farmers. The study recommends that CSBs activities should be rolled-out to other parts of the country through a government financing mechanism that is suggested in the draft national policy on plant genetic resources for food and agriculture. The development of a policy and legal environment that includes an act that has provisions for the recognition of CSBs and the protection of farmers' rights is important. Secondary information, interviews with key informants and Focus Group discussions (FGDs) are the primary sources of data used.